The effect of Tai Chi on elderly depression: a systematic review and meta-analysis of randomized controlled trials - Zhu, Fengya; Wang, Yuan; Yin, Shao; Liu, Junqian; Zhong, Yue; Li, Liuying (Frontiers in Psychology, 2024)
Objective: This systematic review and meta-analysis assess the impact of Tai Chi on emotional well-being and quality of life in elderly individuals with depression.Searching six databases until October 20, 2024, including Embase, PubMed, Cochrane Library, Web of Science, SinoMed, and CNKI, for randomized controlled trials (RCTs). Participants were aged ≥60 and diagnosed with depression. Tai Chi served as the main intervention in the treatment group, with the control group receiving no exercise, or only health education. The primary outcomes focused on the improvement of depressive symptoms and quality of life. Data synthesis and metaanalysis were performed using Stata 15.1 software. The protocol of this study was registered on PROSPERO (ID: CRD42023479305).Results: Tai Chi, as the main intervention, significantly improved depressive symptoms as measured by the Geriatric Depression Scale (WMD = -5.99, 95% CI: -10.80 to -1.19, p = 0.015) compared to no exercise or health education. Subgroup analysis favored a six-month duration of Tai Chi, showing even greater benefits (WMD = -9.79, 95% CI:-13.90 to -5.69, p < 0.001). However, Tai Chi did not demonstrate a significant advantage in improving participants' scores on the Hamilton Depression Scale (WMD = -1.04, 95% CI: -3.84 to 1.76, p = 0.468).Our results indicate that Tai Chi can significantly improve depressive symptoms and quality of life in elderly individuals with depression. As a daily exercise and mind-body therapy to alleviate the mood of the elderly, it is necessary to conduct more large-sample RCTs. Further research on the details of Tai Chi, such as movements, frequency, duration, and exercise periods, is essential for a dose-response relationship, contributing to the standardized promotion of Tai Chi.